(3GdQO Ydi ef jbhd HGdYOO aj TgQ QeVGf hCfg dG jfbU CHOGs - (3GdYcHQj, GdMGQKj, GdHZOGOj, GdcQNj, CHh YHO Gddg, GdTjN GdoepajO, eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe, J (B413s ((3GdfLa GdCTQas)
(3ChdgG (B:s
(3HSe Gddg (B... (3PcQJ CjOc Gddg Cf cJGH CN ef ENhGffG Cgd GdehUd hQO Ydjc jcdac SDGd Yf TgQ QeVGf gd JSYI hYTQjf jheG ceG jchf KdGKjf jheG hgd cGf (B...s
(3BNQgG (B:s
... (3hYed Hg cGaI abgGFge hGSJhOYg GdCFeI Ydjge GdSdGe NGUJge aOd Pdc Ydi Cfg eMV GdMb hdjS ef HGH GdJbjI aj TjA hHGddg GdJhajbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\21s
(3GdPQjYI (B11 - 152( 1253)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis